Wideband antenna pair and its applications for 5G metal frame mobile phones. Issue 13 (2nd September 2021) - Liu, Zheng; Liu, Heng; Huang, Daiwei; Du, Zhengwei
Abstract : A wideband antenna pair used for 5G mobile phones is proposed in this paper. Both elements of the antenna pair consisting of an open slot and a coupled feeding line can cover the band of 3.3–6 GHz, and the isolation is larger than 10 dB. The ground clearance and the total size are 1.5 mm and 30 mm × 1.5 mm × 7 mm, respectively. Using the antenna pair, four- and eight-element multiple-input–multiple-output (MIMO) antennas are constructed. The simulated results show that the proposed antenna pair can be used to construct MIMO antennas for 5G metal frame mobile phones. As an example, the four-element MIMO antenna is manufactured and tested. The measured results show that the four elements can cover the band of 3.3–6 GHz, and the n77, n78, n79, and 5 GHz WLAN bands are covered. At the working bands, the measured efficiencies and isolations are bigger than 46% and 11.4 dB, respectively.